1979
DOI: 10.1111/j.1600-0447.1979.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective disorders and ABO blood types

Abstract: Results of the present study provide evidence of: 1) a positive association between bipolar affective disorder and blood type O and a corresponding negative association between the former and blood type A, 2) a positive association between unipolar affective disorder and blood type O, and 3) a positive association between involutional depression and blood type A and a corresponding negative association between the former and blood types B and O. Sex does not appear to modify the ABO blood types' distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
4
0
3
Order By: Relevance
“…The results obtained with regard to the association between unipolar affec tive disorder and phenotype A [Shapiro et al, 1977] as well as those regarding the bi polar affective disorder and phenotype O [Parker et al, 1961;Masters, 1967;Mendlewiczet al, 1974;Shapiro et al, 1977;Rinieris et al, 1979;Singh et al, 1979] are in agreement with some previous studies. Re garding the distribution of haptoglobin genotypes, there is an increase of homozy gotes (2-2) and decrease of heterozygotes (2-1) in bipolar affective disorder (table II).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results obtained with regard to the association between unipolar affec tive disorder and phenotype A [Shapiro et al, 1977] as well as those regarding the bi polar affective disorder and phenotype O [Parker et al, 1961;Masters, 1967;Mendlewiczet al, 1974;Shapiro et al, 1977;Rinieris et al, 1979;Singh et al, 1979] are in agreement with some previous studies. Re garding the distribution of haptoglobin genotypes, there is an increase of homozy gotes (2-2) and decrease of heterozygotes (2-1) in bipolar affective disorder (table II).…”
Section: Resultssupporting
confidence: 81%
“…The unipolar affective dis order was found associated with blood group A [Shapiro el al., 1977], blood group B [Beckman et al, 1978b] and blood group O [Rinieriset al, 1979]. On the other hand, some investigators have failed to reveal any relationship between affective disor ders and ABO blood groups [Thomas and Hewitt, 1939;Bourgeois and Trejaut, 1967;Gaekwad et al, 1972;James et al, 1977], Studies have also been reported regard ing the association between affective dis orders and serum protein and red cell en zyme polymorphism [Lange, 1970;Beck man et al, 1978a;Balgir, 1983a], Except for four studies [Shapiro et al, 1977;Beckman et al, 1978a, b;Rinieris et al, 1979;Singh et al, 1979], all other in vestigators have treated manic-depressive psychosis as a single disease entity [for more details see Balgir, 1983b].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, some studies have reported statistical relationships between blood types and other aspects of human personality. For example, several studies have found unusually high rates of manic depression among persons with the O blood type (Mendlewicz, Massart-Guiot, Wilmotte, & Fleiss, 1974;Parker, Theilie, & Spielberger, 1961;Rinieris, Stefanis, Lykouras, & Varsou, 1979;Shapiro, Rafaelsen, Ryder, Svejgaard, & Sorensen, 1977) with one failure to replicate (Masters, 1967). Also, studies have reported unusually high rates of cigarette smoking among persons with Arch Sex Behav (2008) 37:145-149 147 both B and AB blood types (Cohen & Thomas, 1962), a propensity for persons with A blood type to score high on a personality measure of ''tender-mindedness'' (Cattell, Boutourline, Young, & Hundleby, 1964), and high rates of suicide among individuals with O blood type (Voracek, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Οί έρευνες γιά τήν πιθανότητα ύπαρξης συνδυασμού μεταξύ Συναι σθηματικών Ψυχώσεων καί ομάδων αίματος ΑΒΟ, έδωσαν αντιφατικά α ποτελέσματα (Rinieris 1979).…”
Section: μελετες στη βαση γενετικων δεικτωνunclassified